Students’ Experiences In Learning Reported Speech Through Wordwall in Eleventh-Gradeat Senior High School - Hanadi Putri; Ina Daril Hanna; Arisandi Setiyawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to explore students' experiences in learning reported speech through the use of Wordwall in grade XI students at SMAN 2 Pamekasan. The use of game-based media such as Wordwall is expected to address the challenges in teaching complex English grammar. This study uses a descriptive qualitative approach. Participants were selected using purposive sampling. Data were collected through direct observation and in-depth interviews with grade XI students. The collected data were analyzed thematically to identify the experiences, challenges, and benefits perceived by students. The results of the study show that Wordwall makes a positive contribution to learning reported speech. Students show increased engagement, motivation, and understanding of the material, as well as positive emotional responses such as feeling more relaxed and excited. Learning becomes more interactive through hands-on practice and peer-to-peer discussion. However, the study also revealed many specific challenges, notably time pressures that make students rush, grammatical difficulties in changing tenses and pronouns, and technical constraints such as device limitations and internet connections. Thus, the effectiveness of Wordwall is highly dependent on the balanced management of technical and pedagogical challenges, namely between the use of gamification features to increase motivation and the provision of adequate support to overcome students' cognitive and technical barriers.